Collective Grief at School. Bonds and Sensitivities to Pain (Praxis Educativa, 2025)
This article aims to understand the collective elaboration of grief in the school environment based on the suicide of a student. The results of a qualitative study carried out in two secondary schools in peripheral urban areas of the Province of Buenos Aires, Argentina, are presented. The analysis of the testimonies allows us to affirm that when faced with the death of a generational peer, the school enables processes of symbolic reparation by favouring a) the constitution of networks of affective support; b) the learning of sensitivity towards the pain of others. The bonds of solidarity and mutual support in the school network, in a context of individualisation of social life, make it possible to reduce the affective distances between the mourners and to constitute collective narratives of meaning.
Keywords: suicide; grief; affective support; young students; secondary school